Proceedings Against Nazi Collaborators in Soviet Lithuania: Case Analysis - Lastauskienė, Giedrė (Teisė, 2025)
The article examines two criminal proceedings that were conducted in Lithuania in 1962, and were concluded regarding individuals who had served in Lithuanian police battalions during World War II and participated in various battalion campaigns (including the mass killings of civilians, most of whom were Jews) being sentenced to death.The 1962 trials took place after the criminal law reform that was carried out in the Soviet Union in 1957–1961. The new criminal laws explicitly prohibited the retroactive application of laws that increased criminal liability; they also established statutes of limitations for prosecution and prohibited the imposition of the death penalty if the maximum statute of limitations (15 years) had expired.In the criminal proceedings in question, the individuals were convicted of treason for adherence to the enemy. In the trials investigated, the individuals were not convicted of being involved in genocide as defined in the Genocide Convention.The fact that the cases contained two secret documents adopted before the commencement of the trial that allowed the courts not to commute the death penalty to imprisonment, that all of the individuals were sentenced to death even though the criminal laws prohibited this, and that these public criminal proceedings were organised by a group consisting of top party, law enforcement and propaganda officials gives reason to believe that these proceedings may have been intended not only to punish individuals who collaborated with the Nazis and participated in police battalion campaigns, but also for other purposes, such as ideology or propaganda.
Keywords: transitional justice; Genocide; Sovietology; Soviet criminal law; retrospective application of laws; judicial independence; right to defence